2020
DOI: 10.1177/2055102920948738
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among Vietnamese urban late adolescents: The association of parenting styles

Abstract: The aim of this study was to explore the correlation between parental styles and mental problems among Vietnamese high school students. In total, 16.4 percent of 757 eligible participants reported mental difficulties. Findings showed that being female and in grade 12 were risk factors to mental problems while living in Hue city was likely as a protective factor. The father’s warmth reduced the risk of having mental problems among adolescents, while an overprotective mother increased the risk. There was no corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Past research in Western cultures found that children are more likely to develop avoidant attachment if they perceive their parents as less warm and more authoritarian (Karavasilis et al, 2003). In Vietnam, fathers are generally less warm and more authoritarian than mothers (La et al, 2020) and use more physical punishment than mothers (Rydstrøm, 2006). It is possible that Vietnamese fathers might be experienced as more consistently unavailable and more a potential source of physical punishment than Vietnamese mothers, in turn resulting in higher levels of avoidant attachment in children.…”
Section: Comparing Vietnamese Adolescents' Attachment Toward Their Mo...mentioning
confidence: 99%
“…Past research in Western cultures found that children are more likely to develop avoidant attachment if they perceive their parents as less warm and more authoritarian (Karavasilis et al, 2003). In Vietnam, fathers are generally less warm and more authoritarian than mothers (La et al, 2020) and use more physical punishment than mothers (Rydstrøm, 2006). It is possible that Vietnamese fathers might be experienced as more consistently unavailable and more a potential source of physical punishment than Vietnamese mothers, in turn resulting in higher levels of avoidant attachment in children.…”
Section: Comparing Vietnamese Adolescents' Attachment Toward Their Mo...mentioning
confidence: 99%